Predicting Stock Closing Price Using Machine Learning Techniques (Journal of Finance, Business and Management Studies, 2024)
Predicting the stock price have been very challenging and profitable task. Since the introduction of artificial intelligence and machine learning techniques, the efficiency of prediction improved to a great extent. An attempt has been made in the present study to predict the closing price of the selected stocks using machine learning and deep neural network techniques. The data of top companies of the Indian stock market for the period from April 2016 to March 2021 have been used. It was obtained that the deep learning model, i.e., LSTM gave better results than the other machine learning model.
Keywords: Machine learning; neural network; Random forest; Support Vector machine; Long-Short term memory